LEXICAL MEANING OF "PAKKAT" YOUNG ROTTAN PLANT IN MANDAILING SOCIETY IN PADANG LAWAS DISTRICT: ECOLINGUISTICS STUDY - Ernita Daulay; Dwi Widayati (JURNAL TARBIYAH, 2021)
Pakkat is a rattan tuber that is still very young and tastes a bit bitter. Young Rottan plants known as "Pakkat" growing in the wilderness are consumed as fresh vegetables or food additives eaten with rice is a traditional food. Mandailing. This study used data that was analyzed descriptively qualitatively using ethnographic methods which aimed to describe completely and thoroughly the young rattan plant "Pakkat" in the Mandailing community in Matondang village, using the approach of observation and interviews with the local community. In the process of collecting field data, the researcher met several informants who knew about Pakkat knowledge. In conducting this research, the authors obtained field data that Pakkat is a typical Mandailing food which is widely believed that those who eat Pakkat will have a high appetite. In addition, Pakkat can also help reduce various types of risks such as heart disease, gout, colds, diarrhea, sugar.